A PRELIMINARY SURVEY OF THE FISH AND FISHERIES OF A FIVE-MILE STRETCH OF THE HOOGHLY RIVER NEAR BARRACKPORE - David, A (Indian Journal of Fisheries, 2016)
A FISHERIES survey of the Hooghly river adjoining Barrackpore area was suggested to the author by Dr. T. J. Job. This survey was felt to be of special significance since the adjoining stretch of the river represents a transitional stage between the typically estuarine conditions lower down and the purely freshwater stretch above